Do Low Hemoglobin Levels Affect the Healing Process of Periprosthetic Joint Infection? - Yaradılmış, Yüksel Uğur (Cureus, 2021)
Background Revision knee arthroplasty (RKA) is associated with low hemoglobin (Hb) levels after surgery, which results mostly from perioperative blood loss. Periprosthetic joint infection (PJI) is one of the common reasons for RKA. This study aimed to determine whether low Hb levels affect the healing process of PJI. Methodology This retrospective study included 69 patients who underwent two-stage revision for PJI between 2013 and 2016. Patients were divided into two groups according to the latest Hb levels (Hb < 10 and Hb > 10 g/dL) during hospitalization for the first-stage revision surgery. Laboratory parameters of infection were measured during the cement spacer retention period: C-reactive protein (CRP), sedimentation rate (SEDIM), and white blood cell (WBC) count. Treatment was evaluated in two periods: cement spacer retention period (between the first surgery and second surgery) and the first normal CRP period (between the first surgery with the first normal CRP level during the cement spacer retention period). Infection parameters in the two time periods and reoperation with cement spacer were compared between the groups. Results The mean patient age was 67.3 ± 7.94 (50-87) years, and the female-to-male ratio was 4:1. No difference was found in the postoperative first control CRP, SEDIM, and WBC between the groups (p = 0.953, p = 0.3341, and p = 0.444, respectively). CRP-SEDIM control curves were observed in parallel, and no significant difference was found. The cement spacer retention period was 60.3 ± 24.8 (17-123) days, and the first normal CRP period was 87.3 ± 28.4 (14-161) days; no statistical difference was found between the groups (p = 0.727, p = 0.754). Conclusions In RKA, as low Hb level was not a negative factor of infection, blood transfusion should be avoided as it has many complications.